Intellectual property licensing and transactions : theory and practice / Jorge L Contreras, University of Utah. - Contreras, Jorge L. (Cambridge University Press, 2022)
Intellectual property transactions underlie large segments of the global economy, from pharmaceuticals to computing, entertainment to digital content. This first-of-its-kind resource combines practical contract drafting and negotiation skills with substantive legal doctrine in the rapidly growing area of intellectual property transactions and licensing. Though primarily designed for classroom use, it is also a must-have legal reference work for every lawyer involved in the technology, biopharma, entertainment, media or financial services industries. It includes practical drafting models and explanations of key contractual provisions such as field of use, exclusivity, milestones, royalties, termination, indemnification and liability, and combines these with discussion of the latest cases interpreting these provisions. Numerous legal doctrines that affect the enforcement of IP agreements are also covered, including exhaustion, first sale, misuse, estoppel, antitrust and bankruptcy law, as well as chapters focusing on specialized fields such as trademark law, music licensing, technical standardization, and IP pooling. This book is also available as Open Access on Cambridge Core.